Bushwhacking : how to get lost in the woods and write your way out - McGaha, Jennifer (Trinity University Press, 2023)
"When you stray from a trail and strike out into the woods, you are bushwhacking. The term implies a physical thrashing about-pushing past branches, slicing through thickets, leaping across downed trees-but it also implies a certain fortitude and resilience to seek places unknown. In Bushwhacking, Jennifer McGaha borrows the term, likening it to what writers do when faced with the equally daunting blank page. Exploring the wilderness of your inner life means leaving a relatively comfortable place and going where no path exists. Writers face similar, unknown obstacles when forging a route to a final draft. Part writing memoir, part nature memoir, and part meditation on a life well lived, Bushwhacking draws on McGaha's experiences running, hiking, biking, paddling, and getting lost across the Appalachian Mountains of western North Carolina to offer readers encouragement practical suggestions to accompany them on their writing and life journeys. With humility, humor, and hard-won wisdom, Bushwhacking honors writing craft traditions and offers fresh insights into how close communion with nature can transform your writing and your life"--